Partisipasi Masyarakat Lokal Dalam Pengelolaan Obyek Wisata Danau Wai Kuri (Studi Kasus Di Desa Kalena Rongo, Kecamatan Kodi Utara, Kabupaten Sumba Barat Daya) - Obet Tanggu; Aris Lambe; Lenny Sofia Bire Manoe (Jurnal Pluralis, 2024)
This study aims to determine the participation of local communities in themanagement of tourist attractions in Lake Wai Kuri and to find out what factorsare the drivers and inhibitors of local community participation in themanagement of Lake Wai Kuri tourist attractions. Lake Wai Kuri has enormouspotential in social and economic aspects. The theory of community participation,which is highly relevant to the problem's topic, guides the analysis of thisresearch. This research employs descriptive qualitative methods and collects datathrough observation, structured interviews, and documentation. The types of datain this research are primary data and secondary data. The analysis resultsindicate that the people of Kaleno Rongo Village have participated well. As acomponent in community-based tourism, local communities have a crucial role insupporting tourism development. The role of local communities in selectingnatural and cultural resources owned is one of the great contributions, and it hasthe potential to become a tourist attraction. Tourist attraction managers leveragethe potential of the local community to contribute to the development, utilizationof economic facilities, and upkeep of cleanliness and security at the Wai KuriLake tourist attraction.